Effects of Manure Levels on Growth and Yield of Yellow Corn in Sandy Soil Under Dry Climate - Elzobair, Khalid; Alkanami, Maryam; Alaswd, Abdalla (Journal of Pure & Applied Sciences, 2018)
A field study was conducted in sandy soil to evaluate the effects of manure levels (0 ton ha⁻¹, 5 ton ha⁻¹, and 10 ton ha⁻¹) on the growth and the yield of yellow corn. Treatments were randomly assigned to nine experimental units (2 m × 2 m) with three replicates. Corn yield, plant height (after 30 days and at harvest), and total organic matter were measured. Results showed that there were not significant effects of manure levels on corn yield or total organic matter at the rates of 5 ton ha⁻¹ and 10 ton ha⁻¹. Results revealed that manure has an effect on plant growth during the early stages of growing, but this effect was not observed at harvest. The outcomes of the study suggested that to exploit such soil, chemical fertilizers, besides organic amendment, should be applied to boost plant growth and yield in the short term.